The effect of thermo-mechanical loading on fracture-related parameters of austenitic steel. (November 2017) - Lyubimova, Lyudmila L.; Tashlykov, Alexander A.; Tabakaev, Roman B.; Levin, Alexander A.; Popov, Aleksey Y.
Abstract: Failure analysis shows that 80–85% of emergency boiler shutdowns at power plants result from heating surface damage. When in service, the tubes are exposed to alternating thermo-mechanical loads, which trigger phase change affecting the individual service life. The service life sometimes differs significantly from its estimated value. This research is based on the hypothesis about the role and influence of internal structural stresses on the actual strength and long-term performance of tube products made of steels and alloys. The purpose of this work is to determine the limit state region of internal stresses of the first kind, in which microdamage will not lead to fracture. For that, we did a set of experiment studies to model the accelerated aging processes by thermal cycling and cold cyclic deformation. We chose a tube made of austenitic steel 10Cr13Mn12Si2Ni2Cu2Nb (Di59) as the object of research. The methods used were XRD analysis, microhardness testing, X-ray spectroscopy, and microstructure analysis. Due to redistributing properties, steel has no stable states: all its states are short-term and dependent on external disturbances. In accordance with the suggested hypothesis, the research findings make it possible to forecast the trends and direction of changes in the material properties. This allows us to evaluate the achievement of the limit state by the object and to use relaxations of internal stresses as a sign determining the conditions of crack initiation and propagation. The results are confirmed by the data obtained from the microstructure analysis of fractured tubes of a superheater from a functioning boiler. Highlights: Steel Di59 was studied by XRD analysis, X-ray spectroscopy, and microhardness testing. Deep relaxation of internal stresses indicates interatomic bond breaking and fracture. The distribution of residual stresses indicated the range of serviceable states.